The Science-Fictionalisation of Globalisation and Image Advertising in Harvest by Manjula Padmanabhan - Priteegandha Naik (Fafnir, 2020)
This article examines the first Indian science-fictional play: Harvest (1998) by Manjula Padmanabhan. It suggests that this dystopic play renders globalisation and image advertisements as novums through new and imagined technologies, and points out that Indian SF has begun to engage with these novums and the associated media technologies, using Harvest as an example of how the novums are used to transform and build fictional worlds.